Electrochemical studies of poly (3,4-ethylenedioxythiophene) PEDOT/VS2 nanocomposite as a cathode material for rechargeable lithium batteries - Murugan, A. Vadivel; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Electrochemistry Communications, 2005)
Here, we demonstrate the electrochemical characterization of a new type of layered poly (3,4-ethylenedioxythiophene) PEDOT/ VS2 nanocomposite. It has been prepared via flocculation of delaminated VS2 with subsequent in situ oxidative polymerization of 3,4-ethylenedioxythiophene (EDOT) with VS2 as a host material in the presence of an external oxidizing agent. The interlayer spacing Of VS2 expands from 5.71 to 14.01 A and this interlayer separation is consistent with the existence of a monolayer of PEDOT in the VS2 framework. X-ray diffraction, XPS and TEM studies have been;shown the change in interlayer separation is consistent with the existence of two phases of organic and inorganic species in the nanocomposites corresponding to the intercalation of PEDOT in the VS2 framework. The application potential of the nanocomposite as a cathode material for rechargeable lithium batteries is also demonstrated by the electrochemical intercalation of lithium into the PEDOT/VS2 nanocomposite, where a significant enhancement in the discharge capacity is observed (similar to130 mAh/g) compared to that (80 mAh/g) for pristine VS2. (C) 2004 Published by Elsevier B.V.
Keywords: layered nanocomposite; lithium batteries; polythiophene; vanadium disulfide

Enhancement of double-layer capacitance behavior and its electrical conductivity in layered poly (3, 4-ethylenedioxythiophene)-based nanocomposites - Murugan, A. Vadivel; Viswanath, A. K.; Campet, Guy; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Applied Physics Letters, 2005)
In this letter, we report on the enhanced double-layer capacitance of a layered poly (3, 4-ethylene dioxythiophene) PEDOT-MoO3 nanocomposite, which has been synthesized by a novel microwave irradiation method. The x-ray photoelectron spectroscopy analysis shows the changes in electron density and the shift in binding energy suggesting charge transfer from sulfur atoms upon PEDOT intercalation between MoO3 layers. The room-temperature conductivity for the PEDOT-MoO3 composite is found to be 1.82x10(-1) S cm(-1), which is four orders of magnitude higher than that of the pristine oxide (3.78x10(-5) S cm(-1)). The enhanced double-layer capacitance of the PEDOT-MoO3 nanocomposite (similar to 300 F g(-1)) compared to that (similar to 40 mF g(-1)) of pristine MoO3 is attributed to higher electronic conductivity, enhanced bidimensionality, and increase in surface area of the nanocomposite.

Entrapment of poly(3,4-ethylenedioxythiophene) between VS2 layers to form a new organic-inorganic intercalative nanocomposite - Murugan, A. Vadivel; Quintin, M.; Delville, M. H.; Campet, Guy; Vijayamohanan, K. (Journal of Materials Chemistry, 2005)
Here we report the synthesis and characterization of a new class of nanocomposite by direct in situ oxidative polymerization of 3,4-ethylenedioxythiophene (EDOT) with VS2 as a host material in the presence of an external oxidizing agent. Upon intercalation, the interlayer spacing of VS2 expands from 5.71 Angstrom to 14.01 Angstrom, followed by exfoliation and a restacking process facilitating expansion of the lattice in a direction perpendicular to the dichalcogenide layers. This change in interlayer separation is consistent with the existence of two phases of organic and inorganic species in the nanocomposites corresponding to the intercalation of PEDOT in the VS2 framework. The resulting nanocomposite is characterized by thermal analysis (TGA), X-ray diffraction, FTIR, SEM, TEM, and four-probe electrical conductivity measurements. The application potential of the nanocomposite as a cathode material for rechargeable lithium batteries is also demonstrated by the electrochemical intercalation of lithium into the PEDOT-VS2 nanocomposite, where a significant enhancement in the discharge capacity is observed (similar to130 mA h g(-1)) compared to that (80 mA h g(-1)) for pristine VS2.

Phase transitions in octanethiol-capped Ag nanocluster microfilm assemblies - Ellis, A.; D'Arcy-Galla, J.; Vijayamohanan, K.; Goswami, R.; Ganesan, P. G.; Ryu, C.; Ramanath, G. (Thermochimica Acta, 2005)
We describe phase transitions in microfilm assemblies of octanethiol (OT)-capped 2-4 nm-diameter Ag nanoclusters prepared from solutions with OT/Ag+ ratios of similar to50. Using DSC we observe two melting/crystallization-type reversible phase transitions: one at similar to61 degreesC due to interdigiated unattached octanethiol, and the other at similar to125 degreesC due to the phase comprised of the assembly of OT-capped nanoclusters. Increased thermal fluctuations weaken the inter-chain hydrophobic interactions between interdigitated OT molecules, leading to both phase transitions. The thiolate bond of OT-molecules bound to Ag nanoclusters are more rigid, thereby requiring a higher temperature to increase the flexibility of the alkyl chain of OT, and to melt the nanocluster assembly. The mobility of the nanoclusters in the melt is limited, and morphological features of the original assemblies are retained during recrystallization. No observable mass loss is detected up to similar to180 degreesC, above which OT molecules desorb from the Ag nanoclusters. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: differential thermal analysis; infrared spectroscopy; phase transitions; silver nanoclusters

Preparation and characterization of composite electrodes of coconut-shell-based activated carbon and hydrous ruthenium oxide for supercapacitors - Dandekar, M. S.; Arabale, G.; Vijayamohanan, K. (Journal of Power Sources, 2005)
The relationship between the structure-specific capacitance (F g(-1)) of a composite electrode consisting of activated coconut-shell carbon and hydrous ruthenium oxide (RuOx(OH)(y)) has been evaluated by impregnating various amounts of RuOx(OH)(y) into activated carbon that is specially prepared with optimum pore-size distribution. The composite electrode shows an enhanced specific capacitance of 250 F g(-1) in 1 M H2SO4 with 9 wt.% ruthenium incorporated. Chemical and structural characterization of the composites reveals a homogeneous distribution of amorphous RuOx(OH)(y) throughout the porous network of the activated carbon. Electrochemical characterization indicates an almost linear dependence of capacitance on the amount of ruthenium owing to its pseudocapacitive nature. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: activated carbon; Composite; Electrochemical characterization; pseudocapacitance; specific capacitance; supercapacitor

Study of correlation of structural and surface properties with electrochemical behaviour in carbon aerogels - Hebalkar, Neha; Arabale, G.; Sainkar, S. R.; Pradhan, S. D.; Mulla, Imtiaz S.; Vijayamohanan, K.; Ayyub, P.; Kulkarni, S. K. (Journal of Materials Science, 2005)
Carbon aerogel is a promising material for electrochemical double layer capacitors. In this paper carbon aerogels prepared by subcritical drying method are investigated for the change in the structure and surface properties at different pyrolysis temperatures. The important relations between structure, morphology, surface area and electrical properties were studied using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), surface area measurement and cyclic voltametry. It is shown that structure and the surface functional groups play important role in enhancement of electrochemical capacitance. The specific capacitance achieved was 114 F/gm which is quite large value for subcritically prepared carbon aerogels without any kind of activation process. (c) 2005 Springer Science + Business Media, Inc.

Wet-chemical templateless assembly of metal nanowires from nanoparticles - Maddanimath, Trupti; Kumar, Anil; D'Arcy-Galla, J.; Ganesan, P. G.; Vijayamohanan, K.; Ramanath, G. (Chemical Communications, 2005)
We describe a new, simple, room-temperature wet-chemical approach for assembling Au and Ag nanoparticles into nanowire networks, without the use of lithographic templates. Five to 35 nm-diameter nanowires passivated with a thin organic layer were synthesized by mechanically agitating a biphasic liquid mixture of an aqueous hydrosol containing the nanoparticles, and toluene. Nanowire structure and surface chemistry are discussed based on electron microscopy, UV-visible spectroscopy and thermogravimetric analyses.

Electrochemical organization of monolayer protected gold nanoclusters on single-walled carbon nanotubes: significantly enhanced double layer capacitance - Mahima, Subhramanyam; Chaki, N. K.; Sharma, J.; Kakade, Bhalchandra A.; Pasricha, R.; Rao, A. M.; Vijayamohanan, K. (Journal of Nanoscience and Nanotechnology, 2006)
This paper reports a novel electrochemical route for anchoring monolayer protected gold nanoclusters (size 8 +/- 0.2 nm) on single-walled carbon nanotube bundles, resulting in the formation of hybrid materials. Monolayer protected gold nanoclusters prepared by modified Brust synthesis route were organized on SWNT bundles by cycling-the potential in dichloromethane between -1 to +1 V at a scan rate of 50 mV/s. Monolayer protected nanoclusters in electrolyte solutions possess ionic space charge around them (double layer charging), making them suitable for organization on nanotube bundles, by tuning the electrostatic interactions. More significantly, analysis of the double layer capacitance of these hybrid materials shows almost ten times increase in capacitance compared to that of bare SWNT bundles. We believe that these hybrid materials are potentially useful in nanoelectronics.
Keywords: double layer capacitance; double layer charging; hybrid materials; monolayer protected gold nanoclusters; single-walled carbon nanotubes

Exfoliation-induced nanoribbon formation of poly(3,4-ethylene dioxythiophene) PEDOT between MoS2 layers as cathode material for lithium batteries - Murugan, A. Vadivel; Quintin, M.; Delville, M. H.; Campet, Guy; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Journal of Power Sources, 2006)
A new type of layered nanocomposite synthesized by delaminated MoS2 nanosheets and poly(3,4-ethylenedioxythiophene) (PEDOT) are restacked to produce alternate polymer nanoribbons between layers Of MoS2 with an interlayer distance of similar to 1.38 nm. The unique properties of resulting nanocomposite are investigated by powder XRD, XPS, SEM, TEM, and four-probe conductivity measurements. The obtained nanocomposite can be used as a cathode material for a small power rechargeable lithium battery as demonstrated by the electrochemical insertion of lithium into the PEDOT/MoS2 nanocomposite. A significant enhancement in the discharge capacity (100 mAh g(-1)) is observed compared with that (40 mAh g(-1)) for MoS2. (c) 2005 Elsevier B.V All rights reserved.
Keywords: cathode material; lithium batteries; MoS2; organic-inorganic nanocomposite; PEDOT-nanoribbons

Highly efficient organic-inorganic poly(3,4-ethylenedioxythiophene)-molybdenum trioxide nanocomposite electrodes for electrochemical supercapacitor - Murugan, A. Vadivel; Viswanath, Annamraju Kasi; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Journal of Applied Physics, 2006)
In this paper, we report a highly efficient organic-inorganic nanocomposite electrode with enhanced double layer capacitance, which has been synthesized using 3,4-ethylenedioxythiophene and crystalline molybdenum trioxide (MoO3) in the presence of an external oxidizing agent. The interlayer spacing of MoO3 upon intercalation expands from 6.93 to 13.46 A and is followed by an exfoliation and restacking process. The resulting nanocomposite is characterized by powder x-ray diffraction, scanning electron microscopy, transmission electron microscopy, x-ray photoelectron spectroscopy, and four probe conductivity measurements. The application potential of this nanocomposite as an electrode material for electrochemical supercapacitors has been investigated, highlighting the unusual enhancement of double layer capacitance of poly(3,4-ethylenedioxythiphene) (PEDOT-MoO3) nanocomposites (similar to 300 F g(-1)) compared to that of pristine MoO3 (similar to 40 mF g(-1)). The improved electrochemical performance is attributed to the intercalation of electronically conducting PEDOT between MoO3 layers with enhanced bidimensionality and an increase in the surface area. (c) 2006 American Institute of Physics.

ZnO multipods, submicron wires, and spherical structures and their unique field emission behavior - Ramgir, Niranjan S.; Late, Dattatray J.; Bhise, Ashok B.; More, Mahendra A.; Mulla, Imtiaz S.; Joag, Dilip S.; Vijayamohanan, K. (Journal of Physical Chemistry B, 2006)
A simple method of vapor deposition for the shape selective synthesis of ZnO structures, namely, multipods, submicron wires, and spheres, has been successfully demonstrated. A plausible growth mechanism based on the studies of scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) is proposed. Our studies suggest that the growth of a multipod structure is governed by the screw dislocation propagation while the vapor-liquid-solid (VLS) mechanism is responsible for the formation of submicron wires and spheres. Moreover, the flow rate of the carrier gas plays a crucial role in governing the morphology. Further, these structures exhibit an enhanced field emission behavior. The nonlinearity in the Fowler-Nordheim (F-N) plot, a characteristic feature of electron emission from semiconductors, is explained by considering the contributions from both the conduction and the valence bands of ZnO.

Cyclic voltammetry, electrochemical impedance and ex situ X-ray diffraction studies of electrochemical insertion and deinsertion of lithium ion into nanostructured organic-inorganic poly(3,4-ethylenedioxythiophene) based hybrids - Murugan, A. Vadivel; Reddy, M. V.; Campet, Guy; Vijayamohanan, K. (Journal of Electroanalytical Chemistry, 2007)
In this work, we discuss the electrochemical insertion and deinsertion of lithium into poly(3,4-ethylenedioxythiophene) PEDOT-V(2)O(5) nanohybrids by using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and powder ex situ X-ray diffraction (XRD) studies with special emphasis on their application potential as cathode materials for rechargeable Lithium batteries. The interlayer spacing of crystalline V(2)O(5) expands from 0.43 to 1.41 nm by the intercalation of PEDOT nanoribbons prepared by a microwave irradiation method. Cyclic voltammetry studies of PEDOT-V(2)O(5) hybrid at a slow scan rate of 0.058 mVs(-1) between 2.0-4.3 V vs. Li/ Li(+), demonstrates that structural transitions Of V(2)O(5) are suppressed and more facile intercalation features appear in terms of well-defined reversible cathodic and anodic peaks when compared to that at higher scan rate. Electrochemical Impedance studies of PEDOT-V(2)O(5) hybrid as cathode at ambient temperature with lithium metal foil as both counter and reference electrodes in 1 M LiPF(6) in a mixture of ethylene and diethylcarbonate (50:50 by volume) between the range 2.0-4.3 V reveals the usefulness of these materials. The observed capacity fading during cycling in terms of surface passivation and structural transformations is also investigated by CV, EIS and XRD analysis. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: cyclic voltammetry; ex situ XRD studies; high capacity lithium batteries; impedance studies; nanostructured hybrid materials

2(7-3) fractional factorial optimization of polybenzimidazole based membrane electrode assemblies for H-2/O-2 fuel cells - Kannan, Ramaiyan; Islam, Md. Nazrul; Rathod, D.; Vijay, M.; Kharul, Ulhas K.; Ghosh, P. C.; Vijayamohanan, K. (Journal of Applied Electrochemistry, 2008)
We describe the usefulness of a statistical fractional factorial design to obtain consistent and reproducible behavior of a membrane-electrode-assembly (MEA) based on a phosphoric acid (PA) doped polybenzimidazole (PBI) membrane, which allows a H-2/O-2 fuel cell to operate above 150 degrees C. Different parameters involved during the MEA fabrication including the catalyst loading, amount of binder, processing conditions like temperature and compaction load and also the amount of carbon in the gas diffusion layers (GDL) have been systematically varied according to a 2(7-3) fractional factorial design and the data thus obtained have been analyzed using Yates's algorithm. The mean effects estimated in this way suggest the crucial role played by carbon loading in the gas diffusion layer, hot compaction temperature and the binder to catalyst ratio in the catalyst layer for enabling continuous performance. These statistically designed electrodes provide a maximum current density and power density of 1,800 mA cm(-2) and 280 mW cm(-2), respectively, at 160 degrees C using hydrogen and oxygen under ambient pressure.
Keywords: Carbon loading; Fractional factorial optimization; MEA; PBI; PEMFC

Effect of synthesis procedure on the structure and properties of palladium/polycarbonate nanocomposites - Valmikanathan, O. P.; Ostroverkhova, O.; Mulla, Imtiaz S.; Vijayamohanan, K.; Atre, S. V. (Polymer, 2008)
In this paper, we compare two procedures for the synthesis of palladium (Pd)/polycarbonate (PC) nanocomposites as well as their morphological, optical, thermal and electrical properties. Pd nanoclusters were produced by the reduction of palladium chloride using a variation of Brust's method. Discrete I'd nanoclusters of similar to 15 nm size were formed in the absence of PC in the reaction mixture (ex situ method) while agglomeration of Pd nanoclusters was noticed in the presence of PC in the reaction mixture (in situ method). Fourier transform infrared spectroscopy (FTIR) suggests nanoparticle-polymer interactions and polymer conformational changes in the in situ nanocomposite films. Even after having the same Pd content, the ex situ nanocomposites films were found to transmit more light than the in situ nanocomposites. The glass transition temperature (T-g), decreased by similar to 16 degrees C for both the ex situ and in situ samples. Thermogravimetric analysis (TGA) indicated that the presence of Pd nanoclusters significantly improved the thermal stability of the nanocomposites, as evidenced by the enhanced onset of degradation by similar to 20 degrees C and similar to 40 degrees C for the in situ and ex situ nanocomposites, respectively. The electrical conductivity measurement shows a dramatic difference between these nanocomposites with a significantly higher value for the in situ nanocomposite (resistivity = 2.1 X 10(5) Omega m) compared to the ex situ nanocomposite (resistivity = 7.2 x 10(13) Omega m). (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: in situ and ex situ syntheses; Morphology; Nanocomposites

Silicate nanoparticles by bioleaching of glass and modification of the glass surface - Kulkarni, Sneha; Syed, Asad; Singh, Sanjay; Gaikwad, Anil; Patil, Kashinath; Vijayamohanan, K.; Ahmad, Absar; Ogale, Satishchandra (Journal of Non-Crystalline Solids, 2008)
Bioleaching is examined as a low temperature (50 degrees C) soft chemical approach to nanosynthesis and surface processing. We demonstrate that fungus based bioleaching of borosilicate glass enables synthesis of nearly monodispersed ultrafine (similar to 5 +/- 0.5 nm) silicate nanoparticles. Using various techniques such as X-ray diffraction, X-ray photoelectron spectroscopy and FTIR we compare the constitution and composition of the nanoparticles with that of the parent glass, and establish the basic similarities between the two. The bioleaching process is shown to enhance the non-bridging oxygen component and correspondingly influence the Si-O-Si network. The root mean square roughness of glass surface is seen to increase from 1.27 nm for bare glass to 2.52 nm for 15 h fungal processed case, this increase being equivalent to that for glass annealed at 500 degrees C. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Bioglass; Biomaterials; borosilicates; narroparticles

Enhanced conversion efficiency in dye-sensitized solar cells based on hydrothermally synthesized TiO2-MWCNT nanocomposites - Muduli, Subas; Lee, Wonjoo; Dhas, Vivek V.; Mujawar, Sarfraj; Dubey, Megha; Vijayamohanan, K.; Han, Sung-Hwan; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2009)
A 50 % enhancement in the conversion efficiency (4.9-7.37 %) is realized in dye-sensitized solar cells Using hydrothermally synthesized TiO2-multiwalled carbon nanotube (MWCNT) nanocomposites as compared to hydrothermally synthesized TiO2 without MWCNT and Degussa P25. Several characterizations have been employed to reveal the nature of the modification imparted to the MWCNTs under hydrothermal processing conditions and the resulting TiO2-MWCNT conjugation through -COOH groups. Efficient charge transfer In the nanocomposite and efficient electron transport by MWCNT (significantly higher Incident-photon-to-current conversion efficiency) are suggested to be the possible reasons for the enhancement.
Keywords: Carbon nanotubes; charge transfer; Dye-sensitized solar cells; Hybrid composite; hydrothermal

Direct transfer of micro-molded electrodes for enhanced mass transport and water management in PEMFC - Deshmukh, Ashvini B.; Kale, Vinayak S.; Dhavale, Vishal M.; Sreekumar, K.; Vijayamohanan, K.; Shelke, Manjusha V. (Electrochemistry Communications, 2010)
Soft lithography technique is used to micropattern the electrodes on the electrolyte membrane of polymer electrolyte fuel cell (PEMFC) in order to alleviate the issues due to poor water management and inadequate reactant distribution in the fuel cell environment. Membrane electrode assembly with the micropatterned electrode has shown an increase in power density at a higher temperature as well as at a higher relative humidity when compared to a flat electrode. Consistency in cell performance is observed in the case of micropatterned electrodes. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Bipolar plate-less PEM fuel cell; Micropatterned electrodes; Microtransfer molding; Soft lithography

Comparative behavior of CdS and CdSe quantum dots in poly (3-hexylthiophene) based nanocomposites (vol 41, pg 198, 2006) - Sonar, Prashant; Sreenivasan, K. P.; Maddanimath, Trupti; Vijayamohanan, K. (Materials Research Bulletin, 2011)

TiO2-Au plasmonic nanocomposite for enhanced dye-sensitized solar cell (DSSC) performance - Muduli, Subas; Game, Onkar S.; Dhas, Vivek V.; Vijayamohanan, K.; Bogle, Kashinath A.; Valanoor, N.; Ogale, Satishchandra B. (Solar Energy, 2012)
Anatase TiO2 nanoparticles dressed with gold nanoparticles were synthesized by hydrothermal process by using mixed precursor and controlled conditions. Diffused Reflectance Spectra (DRS) reveal that in addition to the expected TiO2 interband absorption below 360 nm gold surface plasmon feature occurs near 564 nm. It is shown that the dye sensitized solar cells made using TiO2-Au plasmonic nanocomposite yield superior performance with conversion efficiency (CE) of similar to 6% (no light harvesting), current density (J(SC)) of similar to 13.2 mA/cm(2), open circuit voltage (V-oc) of similar to 0.74 V and fill factor (FF) 0.61; considerably better than that with only TiO2 nanoparticles (CE similar to 5%, J(SC) similar to 12.6 mA/cm(2), V-oc similar to 0.70 V, FF similar to 0.56). (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Anatase TiO2; Au; Dye-sensitized solar cells; Hybrid composite; hydrothermal